Biofertilization and Bioremediation—How Can Microbiological Technology Assist the Ecological Crisis in Developing Countries? - Christine C. Gaylarde; Estefan M. da Fonseca (Micro, 2025)
The increasing global demand for food caused by a growing world population has resulted in environmental problems, such as the destruction of ecologically significant biomes and pollution of ecosystems. At the same time, the intensification of crop production in modern agriculture has led to the extensive use of synthetic fertilizers to achieve higher yields. Although chemical fertilizers provide essential nutrients and accelerate crop growth, they also pose significant health and environmental risks, including pollution of groundwater and other bodies of water such as rivers and lakes. Soils that have been destabilized by indiscriminate clearing of vegetation undergo a desertification process that has profound effects on microbial ecological succession, impacting biogeochemical cycling and thus the foundation of the ecosystem. Tropical countries have positive aspects that can be utilized to their advantage, such as warmer climates, leading to increased primary productivity and, as a result, greater biodiversity. As an eco-friendly, cost-effective, and easy-to-apply alternative, biofertilizers have emerged as a solution to this issue. Biofertilizers consist of a diverse group of microorganisms that is able to promote plant growth and enhance soil health, even under challenging abiotic stress conditions. They can include plant growth-promoting rhizobacteria, arbuscular mycorrhizal fungi, and other beneficial microbial consortia. Bioremediators, on the other hand, are microorganisms that can reduce soil and water pollution or otherwise improve impacted environments. So, the use of microbial biotechnology relies on understanding the relationships among microorganisms and their environments, and, inversely, how abiotic factors influence microbial activity. The recent introduction of genetically modified microorganisms into the gamut of biofertilizers and bioremediators requires further studies to assess potential adverse effects in various ecosystems. This article reviews and discusses these two soil correcting/improving processes with the aim of stimulating their use in developing tropical countries.